Agreement Between Parental Report and Clinician Observation of Infant Developmental Skills - Federico, Alexis; Shi, Dexin; Bradshaw, Jessica (Frontiers in Psychology, 2021)
Understanding the convergence between parent report and clinician observation measures of development is important and became even more critical during the COVID-19 pandemic as clinician contact with families was significantly limited. Previous research points to inconsistencies in the degree of agreement between parents and clinicians and very little research has examined these associations for infants within the first year of life. This study investigated the association between parent report and clinician observation measures of social communication and motor skills in 27 young infants who were assessed at 9 and 12 months of age. Results suggest a strong relation between clinician and parent rated motor skills, but weak to moderate associations between clinician and parent rated communication skills. Infant temperament played a significant role in parent ratings of infant communication. Together, these results provide support for data collection via parent report or clinician observation of infant motor skills, but suggest that multiple measures of infant communication may be helpful to obtain high-quality, perhaps more accurate, assessment social-communication skills. Specifically, multiple parent report measures along with an observation of parent-infant interactions will likely provide a more rich and accurate characterization of infant social-communication abilities.